(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Ni(II) complexes of Schiff’s base macrocyclic ligands i.e. 2,3,9,10-tetraphenyl-1,4,8,11- tetraazacyclotetradeca-1,3,8,10-tetraene (BDP), 2,4,10,12-tetramethyl-1,5,9,13 tetraazacyclohexadeca-1,4,9,12-tetraene (ADP) and 2,3,9,10-tetramethyl-1,4,8,11 tetraazatetradeca-1,3,8,10-tetraene (DDP) have been synthesized. All these synthesized complexes have been characterized by elemental analysis, molar conductance, magnetic susceptibility measurement, IR and UV-Visible spectral studies. On the basis of elemental analysis, the complexes have been found to have the general composition Ni(Lig)X2 where Lig = BDP, ADP, DDP and X = Cl-, SO42- and NCS-. Molar conductance of complexes has been measured in DMSO solvent and the obtained values indicate non-electrolytic nature of all complexes i.e. counter ions are present inside the coordination sphere. Magnetic moments and electronic spectral data suggested six coordinated octahedral geometry for the Ni(II) complexes. The ligand field parameters have been calculated for metal complexes by using various energy level diagrams. In vitro synthesized complexes have been examined against the growth of the some plant pathogenic fungi in order to assess their microbial properties.